Cyclophilin inhibitors restrict Middle East respiratory syndrome coronavirus via interferon-λ in vitro and in mice. Issue 5 (26th November 2020) - Sauerhering, Lucie; Kupke, Alexandra; Meier, Lars; Dietzel, Erik; Hoppe, Judith; Gruber, Achim D.; Gattenloehner, Stefan; Witte, Biruta; Fink, Ludger; Hofmann, Nina; Zimmermann, Tobias; Goesmann, Alexander; et al.
While severe coronavirus infections, including Middle East respiratory syndrome coronavirus (MERS-CoV), cause lung injury with high mortality rates, protective treatment strategies are not approved for clinical use. We elucidated the molecular mechanisms by which the cyclophilin inhibitors cyclosporin A (CsA) and alisporivir (ALV) restrict MERS-CoV to validate their suitability as readily available therapy in MERS-CoV infection. Calu-3 cells and primary human alveolar epithelial cells (hAECs) were infected with MERS-CoV and treated with CsA or ALV or inhibitors targeting cyclophilin inhibitor-regulated molecules including calcineurin, nuclear factor of activated T-cells (NFATs) or mitogen-activated protein kinases. Novel CsA-induced pathways were identified by RNA sequencing and manipulated by gene knockdown or neutralising antibodies. Viral replication was quantified by quantitative real-time PCR and 50% tissue culture infective dose. Data were validated in a murine MERS-CoV infection model. Both CsA and ALV reduced MERS-CoV titres and viral RNA replication in Calu-3 cells and hAECs, improving epithelial integrity. While neither calcineurin nor NFAT inhibition reduced MERS-CoV propagation, blockade of c-Jun N-terminal kinase diminished infectious viral particle release but not RNA accumulation. Importantly, CsA induced interferon regulatory factor 1 (IRF1), a pronounced type III interferon (IFNλ) response and expression of antiviral genes. Downregulation of IRF1 or IFNλ increased MERS-CoV propagation in the presence of CsA. Importantly, oral application of CsA reduced MERS-CoV replication in vivo, correlating with elevated lung IFNλ levels and improved outcome. We provide evidence that cyclophilin inhibitors efficiently decrease MERS-CoV replication in vitro and in vivo via upregulation of inflammatory antiviral cell responses, in particular IFNλ. CsA might therefore represent a promising candidate for treating MERS-CoV infection. The cyclophilin inhibitors cyclosporin A and alisporivir activate host innate immunity by induction of interferon-λ via activation of IRF1 in human lung epithelial cells and in vivo, resulting in a significant inhibition of MERS-CoV https://bit.ly/37gzIBH